2009
DOI: 10.1192/bjp.bp.108.052217
|View full text |Cite
|
Sign up to set email alerts
|

Family participation in treatment, post-discharge appointment and medication adherence at a Nigerian psychiatric hospital

Abstract: In low-income countries, clinicians must seek strategies to improve treatment adherence that are non-resource intensive and easily integrated into existing treatment structures. We conducted a prospective observational cohort study to investigate the relationship of family engagement in treatment during hospitalisation with post-discharge appointment and medication adherence in 81 patients from a Nigerian psychiatric hospital. After controlling for gender, diagnosis, mental state at discharge, and marital stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 11 publications
5
23
2
Order By: Relevance
“…Three studies (Conus et al, 2010;Schimmelman et al, 2006;Stowkowy et al, 2012) found a significant (or trending) association between psychotic disorder not otherwise specified (as compared to schizophrenia) and poor attendance. A fourth study (Adeponle et al, 2009) found substance use diagnoses to be associated with poor attendance; this is consistent with the finding that continued substance use during treatment leads to poorer attendance (Conus et al, 2010;Schimmelman et al, 2006;Stowkowy et al, 2012;Turner et al, 2007), which was supported by all four studies investigating this variable. Other more varied results also emerged, indicating mood disorder diagnoses may be associated with better attendance (Turner et al, 2007), as may be schizophrenia (Svettini et al, 1998) and diagnoses other than PTSD (Sparr et al, 1993).…”
Section: Correlates Of Attendancesupporting
confidence: 74%
See 4 more Smart Citations
“…Three studies (Conus et al, 2010;Schimmelman et al, 2006;Stowkowy et al, 2012) found a significant (or trending) association between psychotic disorder not otherwise specified (as compared to schizophrenia) and poor attendance. A fourth study (Adeponle et al, 2009) found substance use diagnoses to be associated with poor attendance; this is consistent with the finding that continued substance use during treatment leads to poorer attendance (Conus et al, 2010;Schimmelman et al, 2006;Stowkowy et al, 2012;Turner et al, 2007), which was supported by all four studies investigating this variable. Other more varied results also emerged, indicating mood disorder diagnoses may be associated with better attendance (Turner et al, 2007), as may be schizophrenia (Svettini et al, 1998) and diagnoses other than PTSD (Sparr et al, 1993).…”
Section: Correlates Of Attendancesupporting
confidence: 74%
“…Ongoing substance use is one variable which seems to consistently predict risk for lowered attendance or dropout; demographic variables and employment seem to be of References of previous related reviews searched 51 potentially relevant articles identified  22 excluded due to inappropriate focus  12 excluded because not enough information was provided  11 excluded because sample was not appropriate  1 excluded because they were unpublished/not peer reviewed  3 excluded because outcome measure was subjective 2 relevant articles included Adelufosi et al, 2013;Adeponle et al, 2009;Conus et al, 2010;Schimmelman et al, 2006;Stowkowy et al, 2012;Svettini et al, 1998;Turner et al, 2007;Ucok et al, 2007 Race/Ethnicity 2 0 n/a Kurtz et al, 2011;Turner et al, 2007 Sex 8 0 n/a Adelufosi et al, 2013;Adeponle et al, 2009;Conus et al, 2010;Kurtz et al, 2011;Schimmelman et al, 2006;Stowkowy et al, 2012;Svettini et al, 1998;Turner et al, 2007 Education 5 Living away from family 6 2 Predicted less attendance (Conus et al, 2010;Schimmelman et al, 2006) Adelufosi et al, 2013;Stowkowy et al, 2012;Svettini et al, 1998;Turner et al, 2007 Distance from service site 2 2 Greater distance predicts less attendance (Adelufosi et al, 2013;Adeponle et al, 2009) Other psychosis diagnosis predicts less attendance as compared to schizophrenia (Conus et al, 2010;Stowkowy et al, 2012); substance use diagnosis predicts less attendance (as compared to affective diagnosis; (Adeponle et al, 2009)); PTSD and/or substance abuse diagnosis predicts less attendance (as compared to schizophrenia, major depression, bipolar, dysthymic disorder …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations